Increasing Adolescents' Knowledge of Family Preparation Through the Use of Audio-Visual Media - Erika Yulita Ichwan (International Journal of Science and Society, 2023)
The high number of marriages and divorces in Indonesia, particularly in the DKI Jakarta area, is caused by the lack of readiness to marry both physically, mentally, and socially to be together in carrying out all of the family's obligations. The purpose of this research is to find out the comparison of knowledge and effectiveness between the use of audio-visual media and lectures on the level of knowledge of young adults about family preparation. This research uses the quasi-experimental method with a cross-sectional design. The population of this study is "Karang Taruna" in the Cipayung District, East Jakarta. The determination of sample size was calculated using a hypothetical test formula of two proportions: the determination of samples with purposive sampling and 33 respondents for audiovisual media and 33 respondents for lectures. The data were tested with statistical tests such as paired t-tests and sample t-tests using the SPSS programme. The results of the study show that there is an influence between audio-visual and lecture methods in family planning on the knowledge of young or early adults, with the method of lectures (p = 0.01) and audio-visual (p = 0.00). There are also significant differences in knowledge between lecture methods and audiovisual methods towards improving young or early adult knowledge about family planning, with a P value of 0.000. The differences in effectiveness have been found for the value of audio-visuals (M value = 41.612 and P value =.001), while the value of lectures is M value = 19,550 and P value =.001. From the result above, it can be concluded that audio-visual have higher effectiveness compared to lectures.